Heparin-induced thrombocytopenia treated with fondaparinux: single center experience - Dulicek, Petr; Ivanova, Eva; Kostal, Milan; Thibaud, Zuzana; Sadilek, Petr; Hirmerova, Jana (International angiology, 2020)
BACKGROUND: Heparin-induced thrombocytopenia (HIT) is the most frequent drug-induced, immune-mediated thrombocytopenia. It is associated with significant morbidity and mortality. Anticoagulation with heparin must be stopped immediately and replaced by some suggested alternative - lepirudin, danaparoid or argatroban. Fondaparinux has been also successfully used in HIT. METHODS: We present a cohort of 10 patients diagnosed with HIT and treated in a university hospital in a period of four years. Diagnosis was based on Keeling ́s scoring system, screening immunologic test for HIT (STic EXPERT® HIT) and sandwich ELISA (detection of IgG/heparin-PF4 antibodies). While other alternative anticoagulants are not readily available in our hospital, we used fondaparinux in all cases. RESULTS: From 2014 to 2018, eight males and two females (mean age 67 years, range 46-86 years) were diagnosed with HIT in our hospital. This complication developed in 9 cases after low-molecular-weight heparin and in one after heparin flushes in hemodialysis. A drop-in platelet count developed in all patients, thrombotic complications in 7 and skin necrosis in 2 cases. Fondaparinux was used in all patients, including two cases with severe renal impairment, the dose was chosen individually. We observed complete platelet recovery in all cases. One patient died because of advanced malignancy, others did not have any complication. In 6 cases we switched to oral anticoagulation after platelet recovery. CONCLUSIONS: In our group of 10 HIT patients fondaparinux was shown to be both safe and effective, even in those with severe renal impairment. Additional studies are warranted to confirm this observation.
Keywords: Blood Coagulation; senioři nad 80 let; heparin nízkomolekulární; Humans; lidé; trombocytopenie; antikoagulancia; lidé středního věku; Thrombocytopenia; Platelet Count; Anticoagulants; Middle Aged; Aged, 80 and over; inhibitory faktoru Xa; Female; Male; mužské pohlaví; počet trombocytů; Aged; Fondaparinux; ženské pohlaví; Severity of Illness Index; Heparin, Low-Molecular-Weight; stupeň závažnosti nemoci; Factor Xa Inhibitors; hemokoagulace; fondaparinux; senioři